Lao PDR Public Expenditure Review - World Bank (World Bank, Washington, DC, 2014)
This Public Expenditure Review starts by looking at the country s macro-fiscal performance in chapter one, it examines the implementation of the Nam Theun 2 (NT2) Revenue Management Arrangements (RMA) by which the government committed itself to continued strengthening of PFM and the selection of eligible pro-poor and environmental conservation projects to be funded from NT2 revenues in chapter two, and takes stock of issues relating to expenditure prioritization and centralization of tax, treasury, and customs department in chapter three on Public Finance In this way, the PER responds to the commitment made to stakeholders in the hydropower dam project that implementation of the RMA would be reported on in successive Public Expenditure Reviews (PER). The PER then review the intergovernmental fiscal arrangements, as they have evolved since the new organic Budget Law was promulgated in 2006. Currently, central, provincial and district governments are considered deconcentrated elements of a single level executive. In practice provincial governors enjoy considerable autonomy, causing variation in the implementation of national policies. The government, however, is moving towards a more transparent, rules based intergovernmental fiscal system. PER-IFA-2007 provided some initial analysis and comments on such a transformation. Finally, Chapter four look in greater detail at the current system of revenue and expenditure assignments and transfers, and how they work in practice. It then discusses the challenges in designing a new system of inter-governmental relations with reduced vertical and horizontal imbalances.